The Role of Employee Performance at Distribution Center PT. Indomarco Prismatama Medan Branch Based on Discipline and Work Environment - Sosroaji, Muhammad Tirto; Syamsuri, Abd. Rasyid; Hutasuhut, Julianto (Garuda Prestasi Nusantara Consulting, 2022)
This study aims to analyze the role of employee performance at the Distribution Center of PT. Indomarco Prismatama Medan Branch based on discipline and work environment. This study used a quantitative research methodology. The 54 participants in this study were all workers at the Distribution Center PT. Indomarco Prismatama Medan Branch. Saturated sampling is the technique employed. Due to the 54 employees who work at the Distribution Center PT. Indomarco Prismatama Medan Branch, all of the employees are used as research subjects. Observation, documentation studies, and questionnaires were the data collection methods employed. Multiple linear regression using the statistical product software solution (SPSS) program is the analytical approach used in this study. The findings of the study demonstrate that, at the Distribution Center of PT. Indomarco Prismatama Medan Branch, discipline has a favorable and significant impact on staff performance. The work environment at the Distribution Center PT. Indomarco Prismatama Medan Branch has a positive and significant impact on employee performance. Employee performance in the Distribution Center of PT. Indomarco Prismatama's Medan Branch is positively and significantly impacted by discipline and the work environment. The adjusted R square value for the coefficient of determination in this study was 0.811, which indicates that the factors of discipline and work environment may account for 81.9% of employee performance. Keywords: Discipline, Work Environment, Employee Performance.